Ways to Achieve World Peace in Light of International Conflict - Hamad, Saddam Marir (Journal of Tikrit University for Humanities, 2024)
There will never be true peace in the world as long as every nation seeks peace only for itself.” Peace will not come to a nation without its neighbor, because today’s world is highly influenced by one another, as a result of technological development, the ease of communication and movement from one country to another, and the close interconnection between global events. The best example of this is the Arab revolutions that occurred in a close period because their circumstances, causes, motives, and the suffering of the peoples were similar. Today's world is full of wars, disasters, and conflicts called (terrorism). It is as if an epidemic suddenly struck human society, which suggests to some that it is directed by major powers that control it and strike whenever they want, wherever they want, at the time they want. Therefore, people must know the motives and reasons behind the operations of terrorism and intimidation that afflict humanity, and find appropriate solutions for salvation from fanaticism and to achieve peace in the world.